1998
DOI: 10.5059/yukigoseikyokaishi.56.863
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Approach for Discovery and Development of Novel Rice Herbicide, Pyriminobac-methyl.

Abstract: A novel synthesis of methyl 6-acetylsalicylate, a key intermediate directed at 6-substituted pyrimidin-2-yl-salicylate herbicides (PS) and their analogues, was studied. Three synthetic approaches were successful. Among them , a regioselective ortholithiation method was the most promising, and was applied for the synthesis of various 6-acylsalicylates and for the commercial synthetic method of Pyriminobac-methyl as well. Using methyl 6-acylsalicylate, 6-acyl pyrimidin-2-yl-salicylates (6-acyl PS) , their acetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Overall both the (−)‐( S ) and the (+)‐( R ) forms of 37 showed about the same level of herbicidal activity relative to the racemate 37 . The relative lack of importance of the chirality is not yet clear, but the existence of a broad variety of the ortho ‐substituent Q throughout the series of compounds A has been widely documented 1–10. Similar observations of the lack of importance of chirality have been made earlier on the enantiomers of 5‐(2‐chloro‐4‐trifluoromethylphenoxy)‐3‐methylphthalide 65.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Overall both the (−)‐( S ) and the (+)‐( R ) forms of 37 showed about the same level of herbicidal activity relative to the racemate 37 . The relative lack of importance of the chirality is not yet clear, but the existence of a broad variety of the ortho ‐substituent Q throughout the series of compounds A has been widely documented 1–10. Similar observations of the lack of importance of chirality have been made earlier on the enantiomers of 5‐(2‐chloro‐4‐trifluoromethylphenoxy)‐3‐methylphthalide 65.…”
Section: Resultsmentioning
confidence: 58%
“…In contrast, the 6‐acylbenzoates IX are easily available by well‐documented procedures from protected 3‐alkylcarbonylphenols26–28 and then re‐esterified to the more stable phthalide forms II and IIc (R 4 = OR). We observed that, in general, all the ketal esters II , IIb , IIc and IA (R 4 = OR) are far less sensitive to acid‐ or base‐catalysed hydrolysis than the corresponding ortho ‐acetyl salicylates IX, IXa and their 6‐acyl‐pyrimidin‐2‐ylthiosalicylate derivatives A ′ that can undergo self‐catalysed rearrangement merely on standing to give the corresponding phthalide forms II , IIb , IIc and IA (R 4 = alkoxy) 8. 9, 27 The 6‐acylsalicylic acids IX (R = H) and the free acid derivatives A ′ (Figs 1 and 3; R = H) are generally isolated as the corresponding 3‐hydroxyphthalide forms IVb , IVc , II (R 4 = OH) and IA (R 4 = OH), as was shown by Finkelstein et al 29 for 3,7‐dihydroxy‐3‐methylphthalide II (R 3 = Me, R 4 = OH).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] In terms of phytotoxicity, there are many reports showing that natural and synthetic isobenzofuranones are plant growth inhibitors (Scheme 1). [18 -28] Phenoxyphthalide and its amino-, oxy-, and thio-derivatives; [20,23,26] chrycolide and rubralides, [22,25] cryphonectric acid [19] and its oxycyclohexenyl derivatives; [27] dihydroxy phthalide; [21] butylidene phthalide; [29] isobenzofuranimines; [18] and 4,7-methanoisobenzofuran-1(3H)-one, [24,27] are among those. Overall, the phytotoxicity level of these compounds depends on applied concentrations and chemical structures as well as tested species.…”
Section: Introductionmentioning
confidence: 99%
“…pyrithiobac, pyriminobac, bispyribac, pyriftalid and pyribenzoxim. All five were developed in the 1990s, and are used to prevent and remove broadleaf weeds in cotton, barnyard grass in rice, Kentucky bluegrass in creeping shears, annual bluegrass and large horsetail, among others. However, long‐term use of these herbicides makes the problem of their resistance increasingly serious .…”
Section: Introductionmentioning
confidence: 99%